Land Banking Policy (Critical Evaluation of the Economic and Social Rights of Traditional Legal Communities) - Isnaeni, Diyan; Hamadi, Abdennour (Universitas Negeri Semarang, 2024)
The problem of land acquisition for customary communities is no longer a contemporary problem, but since massive development there has been a shift in the rights of indigenous communities in managing land. In principle, this has an impact on the property rights and economy of indigenous communities in using land as the most important natural resource in their communities. Therefore, land bank policies and schemes are the most comprehensive policies to protect the land rights of indigenous peoples. The objectives of this research are the concept of protecting land rights as economic property rights of indigenous peoples and policy determination. Land Banking Policy Implications and institutional schemes for implementing Land Banking for indigenous communities in Indonesia. This research is categorized as normative legal research with a philosophical and analytical approach, and analyzed using descriptive analytical methods. The research results show that land rights for indigenous peoples have not been explicitly recognized internationally and nationally, however, the contemporary development of economic ownership rights for customary land is starting to be recognized in several jurisprudence and interpretations. The implications of the land bank policy are carried out and begin with the classification of land objects and strengthening the policies and schemes of land bank institutions.